2012
DOI: 10.1093/infdis/jis510
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Vaccinia: Case Description and Laboratory-Guided Therapy With Vaccinia Immune Globulin, ST-246, and CMX001

Abstract: Progressive vaccinia (PV) is a rare but potentially lethal complication that develops in smallpox vaccine recipients with severely impaired cellular immunity. We describe a patient with PV who required treatment with vaccinia immune globulin and who received 2 investigational agents, ST-246 and CMX001. We describe the various molecular, pharmacokinetic, and immunologic studies that provided guidance to escalate and then successfully discontinue therapy. Despite development of resistance to ST-246 during treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
123
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 20 publications
1
123
1
Order By: Relevance
“…However, no therapeutic is currently licensed by the Food and Drug Administration (FDA) for the treatment of smallpox. A case report described an army recruit diagnosed with acute mylogenous leukemia M0 (AML M0) following vaccination with the ACAM2000 smallpox vaccine that resulted in life-threatening progressive vaccinia (9). The case management demonstrated that even high doses of VIGIV (6 to 24,000 U/kg) together with the investigational antiviral drug tecovirimat (ST-246) failed to ameliorate disease in an immune-deficient patient.…”
mentioning
confidence: 99%
“…However, no therapeutic is currently licensed by the Food and Drug Administration (FDA) for the treatment of smallpox. A case report described an army recruit diagnosed with acute mylogenous leukemia M0 (AML M0) following vaccination with the ACAM2000 smallpox vaccine that resulted in life-threatening progressive vaccinia (9). The case management demonstrated that even high doses of VIGIV (6 to 24,000 U/kg) together with the investigational antiviral drug tecovirimat (ST-246) failed to ameliorate disease in an immune-deficient patient.…”
mentioning
confidence: 99%
“…Clinical trials showed that ST-246 was well tolerated by human subjects after daily oral administration (15). Moreover, ST-246, together with VIGIV and CMX001, was recently successfully used for the treatment of progressive vaccinia, demonstrat-ing the advantage of combination therapy utilizing drugs that target different stages of VACV infection (16).…”
mentioning
confidence: 99%
“…A primary component of the treatment of such infections is vaccinia immune globulin (VIG) (4,5). VIG is expensive and difficult to produce in large quantities.…”
mentioning
confidence: 99%
“…As an example, in 2012, the case of an immunosuppressed military vaccinee with a severe progressive vaccinia infection was reported. The individual was successfully treated, but treatment required 341 vials of VIG over the course of 75 days in addition to oral and topical treatments with tecovirimat (ST-246) and brincidofovir (CMX001, an orally active prodrug of cidofovir [CDV]) (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation